Importance of systematic records and archives management for work efficiency and preservation of cultural heritage : departments responsibilities / Raja Abdullah Raja Yaacob - Raja Yaacob, Raja Abdullah (Faculty of Information Management, 2005)
The overwhelmed increase of recorded information created, by organizations, including government departments has created a dilemma in the records management process. Records management and information management is the main component in establishing an efficient administration. Records is regarded as vital, important and useful resources to any organisation as it has values such as historical, administrative, legal and financial. Records is the strategic resource and knowledge to the organisation and becomes part of the organisation assets. Government department must begin the essential strategies for establishing or improving the records management programs to alleviate the pressure that may be caused by the records explosion. The application of a systematic records management program in the Jabatan is important in that it is in line with the concept of the TWO Es in records management, that is economy and efficiency. This can be achieved by providing qualified and well trained records manager and staff to handle the records management program in the division.